PENGARUH PENGGUNAAN MEDIA SMARTBOARD TERHADAP KEMAMPUAN MENULIS CERITA PENDEK PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS II UPTD SD NEGERI 122349 PEMATANGSIANTAR - Solya Septriana Saragih; Nancy Angelia Purba; Theresia Monika Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using Smartboard media on students’ short story writing skills in Indonesian Language subject in Grade II of UPTD SD Negeri 122349 Pematangsiantar in the 2025/2026 academic year. The background of this research is the low ability of students in writing short stories, particularly in developing ideas, organizing sentences coherently, and using appropriate vocabulary. This research employed a quantitative approach with a Pre-Experimental Design using a One Group Pretest–Posttest Design. The population and sample in this study consisted of all 28 Grade II students, using a total sampling technique. Data were collected through tests, observation, and documentation. The research instrument was a short story writing test that had been validated using Aiken’s V validity index, showing that the instrument was valid. Data analysis was conducted using the Shapiro-Wilk normality test and the paired sample t-test with IBM SPSS Statistics version 24. The results showed that the mean score of the pretest was 48.75, which increased to 81.14 in the posttest. The hypothesis testing results showed a t-value of -9.038 with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that there is a significant effect of using Smartboard media on students’ short story writing skills in Grade II of UPTD SD Negeri 122349 Pematangsiantar. The use of Smartboard media has been proven to improve students’ learning motivation, classroom engagement, and their ability to write short stories in a more structured and creative way.